External governance and economic patriotism in European policies - Eperjesi, Zoltán (Acta Agraria Debreceniensis, 2013)
The concept of external governance tries to define the expanding scope of EU rules beyond EU borders. This article presents the theoretical foundations of the concept, differentiating the various institutional modes according to which external governance may take place. Due to the financial and economic crisis the European Union is forced to strengthen its competitiveness opposite to cohesion. In the second part of the study I present the five mechanisms by which the European Union may foster its position in the global competition. The five mechanisms are as follows: extension of the political space of the EU, expansion of the regulation mechanisms of the EU, active coaching of international organisations, territorial extension of the EU’s influence, division of the costs of globalization. After that I deal with the different forms of economic patriotism. Economic patriotism plays crucial role in maintaining the performance and strengthening the position of some preferred domestic industries, ‘national champions’. Tools of economic patriotism differ due to ideological affinities.